1983
DOI: 10.1002/bit.260250220
|View full text |Cite
|
Sign up to set email alerts
|

The effects of limiting nutrients, dilution rate, culture pH, and temperature on the yield constant and anthocyanin accumulation of carrot cells grown in semicontinuous chemostat cultures

Abstract: With carrot cells grown in semicontinuous culture with phosphate as limiting nutrient. Dougall and Weyrauch (1980) found that the steady-state culture density was different at different dilution rates. They suggested that the yield constant for biomass was different at different dilution rates. Here the yield constant for biomass for PO(4) (3-), NH(4) (+), Mg(2+), and glucose-limited semicontinuous cultures has been measured directly at two dilution rates. The yield constants for PO(4) (3-), NH(4) (+), and Mg(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The correlation shown here between the cessation of anthocyanin accumulation and increasing of medium pH to 5.0-5.2 is supported by the observations that less anthocyanin is accumulated when the pH of the medium is 5.0 or 5.5 compared to pH4.5 in batch cultures [8] and in semicontinuous chemostat cultures [7]. In the medium of these experiments the pH appears to be a result of simultaneous utilization of ammonia (leading to acidification) and of succinate (leading to alkalinization) of the medium.…”
Section: Discussionsupporting
confidence: 66%
“…The correlation shown here between the cessation of anthocyanin accumulation and increasing of medium pH to 5.0-5.2 is supported by the observations that less anthocyanin is accumulated when the pH of the medium is 5.0 or 5.5 compared to pH4.5 in batch cultures [8] and in semicontinuous chemostat cultures [7]. In the medium of these experiments the pH appears to be a result of simultaneous utilization of ammonia (leading to acidification) and of succinate (leading to alkalinization) of the medium.…”
Section: Discussionsupporting
confidence: 66%
“…Temperature dependence may also be a cause of the considerable variations in accumulation rates of consecutive subcultures of several culture periods. Even variations of ± 1 °C lead to temperature differences of 4 °C in the course of a year (Table 178; Dougall et al 1983;Lockwood 1984;Morris 1986). (Table 179) The speed of stirring cultures influences the cells' synthetic productivity (Fig.…”
Section: External Culture Conditionsmentioning
confidence: 99%
“…Tal & Goldberg obtained good cell growth with little steroid synthesis in continuous fermentations of Dioscorea deltoidea [54]. Dougall and coworkers, in culturing Daucus carotaon a continuous basis demonstrated that factors which improve biomass productivity either do not affect product formation or actually inhibit it [104,105]. This naturally leads to a process whereby biomass and product synthesis are uncoupled.…”
Section: Process Systemsmentioning
confidence: 99%